Time-modulated array antennas – theory, techniques, and applications. Issue 12 (13th August 2019) - Rocca, P.; Yang, F.; Poli, L.; Yang, S.
ABSTRACT: This paper aims to present an up-to-date overview of the state-of-the-art about time-modulated arrays ( TMA s). Starting from a description of the TMA fundamentals and basic theory in the time and frequency domain, the most popular techniques for synthesizing TMA s are revised. Afterwards, a survey of the main application contexts in which TMA s have been proposed is reported. Finally, current research trends are discussed and future developments envisaged.